Enhancement of liver mitochondrial complex I and energy metabolism induced by enteritis: The key role of gut microbiota derived endotoxins - Lele Fu; Lele Fu; Haokun Liu; Wen Chen; Wen Chen; Jamie Marie Hooft; Margareth Øverland; Wanjie Cai; Wanjie Cai; Dong Han; Dong Han; Dong Han; et al. (Frontiers in Immunology, 2022)
Inflammation is an energy-intensive process and the liver is a key organ in energy regulation. Since the intestine and liver exchange nutrients and metabolites, enteritis can affect the liver. To investigate the correlation between enteritis and liver metabolism, we developed an intestinal inflammation model with concentration-dependent 2,4,6-trinitrobenzene sulfonic acid (TNBS) in gibel carp (Carassius gibelio). The results showed the dysregulation of intestinal tight junction, increased permeability of the gut barrier, and apoptosis of epithelial cells during the development of enteritis. The liver metabolome was analyzed by LC-MS and the live respiration was determined using Oxygraph-2k. The results showed that glycolysis, the TCA cycle and pyrimidine metabolism were affected by intestinal inflammation. In particular, the activity of hepatic mitochondrial respiratory chain complex I was significantly increased. Structure and abundance changes of gut microbiota were analyzed by 16S rRNA sequencing analysis. Pathogenic bacteria in the intestine, as well as plasma LPS, increased significantly. Using a liver cell line, we verified that the dysfunctional metabolism of the liver is related to the dislocation of LPS. All results imply the existence of a connection between enteritis and liver metabolism in gibel carp, and the gut microbiome plays a critical role in this process.